Perbedaan Jenis Tugas Keluarga Sebagai Penentu Terhadap Fungsi Penglihatan Childhood Di Era Covid-19 - Wahyuningrum, Ari Damayanti; Satiti, Ika Arum Dewi (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
In January-February 2022, there was a surge in Covid-19 cases due to the omicron virus mutation. Consequently, the government advised conducting remote learning for all students using internet-connected devices. Changes in vision function during childhood occurred globally in 2050 children, with 10% of Indonesia's 66 million children experiencing visual impairments. Maintaining eye health in this age group is facilitated through school health units, and the results are reported to parents during each semester's report card distribution. This study aimed to measure the differences in family developmental tasks concerning childhood vision function. The research design employed was a cross-sectional study using descriptive analysis involving 111 respondents: parents and elementary school students selected through accidental sampling. Data collection took place in October 2022. The measurement tool, developed from Dunst (1984), assessed family developmental tasks, converted into the Brinkman index. Student vision was measured using a Snellen card, and the level of difference was assessed using the Kruskal-Wallis test. The Brinkman index results showed that 38.14% had good vision function, 45.35% were adequate, and 16.51% were poor. The hypothesis test yielded a p-value of 0.316 0.05, indicating no significant difference between family developmental tasks and childhood vision function.Top of Form